Information-methodological support on regional library sites - L. M. Rakitskaya (Библиосфера)
The article is devoted to research of library sites implementing methodological support at the regions. The author analyzes special headings structure, purposes of the regional methodological centers, main directions, forms and methods of library activities. The paper shows efficiency of regional sites and their special headings on different directions of libraries methodological support. A priority is the library staff training and retraining. The model site is proposed, which reveals components and functions of special headings for libraries methodological support.